Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Minuman Isotonik Hydro Coco di Desa Berlian Makmur - Antika, Rindiani; Moelyatie, Trisniarty Adjeng; Puspasari , Mardiana (PT Maju Malaqbi Makkarana, 2025)
The purpose of this study was to determine the effect of the marketing mix, both collectively and partially, on purchasing decisions for Hydro Coco isotonic drinks in Berlian Makmur Village. This study used 100 samples, using a non probability sampling technique with purposive sampling. This study was associative, with primary data and a questionnaire as the data collection technique. The analysis techniques used were multiple linear regression, F-test, t-test, and coefficient of determination. The results showed that the marketing mix had a collective effect on purchasing decisions for Hydro Coco isotonic drinks in Berlian Makmur Village. Partially, 1) product (X1) significantly influenced purchasing decisions. 2) price (X2) significantly influenced purchasing decisions. 3) distribution channels (X3) significantly influenced purchasing decisions. 4) promotion (X4) significantly influenced purchasing decisions.